SINKRETISME DALAM SLAMETAN RITUAL ULUR-ULUR - Hakim, Luqman; Yoesoef, M. (UI Scholars Hub, 2023)
This research aims to explain the hidden narrative in the slametan of the ulur-ulur ritual at Telaga Buret, Sawo Village, Campurdarat District, Tulungagung Regency. In 2020, during the Covid-19 pandemic, the long sequences of ulur-ulur rituals were summarized by only conducting slametan. This indicates that the main foundation of the ulur-ulur ritual is slametan. To find the core ideology of slametan, this study employed the ethnographic approach. Data were obtained through participatory research and in-depth interview. The collected data were then transcribed and analyzed using related theories. This research shows that in slametan, syncretic narratives are beautifully woven into the ritual. An assortment of narratives from Islam and other religions or beliefs is represented in the offerings served during the ritual. Each offering is addressed specifically to a particular supernatural entity through ujub. This harmonious assortment shows that the Javanese people have a high degree of adaptability when it comes to adjusting their religious practices to inevitable social changes.